Penerapan Media Pembelajaran Modern Interaktif dalam Mata Pelajaran Fiqih Kelas X - Muhammad Andika Ainur Rofiq; Mohammad Saat Ibnu Waqfin (ANWARUL, 2026)
Advances in information and communication technology have had a significant impact on education, including Islamic Religious Education (PAI), particularly Fiqih instruction. However, suboptimal use of modern instructional media, limitations in facilities and infrastructure, and teachers’ readiness to integrate technology into the learning process remain constraints, which in turn contribute to low student motivation and participation in Fiqih learning. This study aimed to describe the implementation of interactive modern instructional media in Grade X Fiqih learning, identify constraints encountered in its use, and analyze the role of such media in students’ motivation and learning comprehension. The study employed a qualitative approach with a descriptive design, with data collected through observation, interviews, and documentation involving the Fiqih teacher and Grade X students at a Madrasah Aliyah. The findings showed that interactive modern instructional media, such as digital presentations (PowerPoint), instructional videos, and the use of an LCD projector, had been implemented in Fiqih learning and were able to increase students’ attention, motivation, participation, and ease of understanding the material. Nevertheless, implementation remained constrained by limited supporting facilities and limited teacher preparation time. The study concludes that interactive modern instructional media play an important role in improving the quality of Fiqih learning; therefore, support for facilities and infrastructure, as well as enhancement of teacher competence, is needed to ensure that the use of modern instructional media can be more optimal and sustainable.